Measurement of changes in optic nerve sheath diameter using ultrasound and computed tomography scan before and after the ventriculoperitoneal shunt surgery in patients with hydrocephalus - A prospective observational trial. (4th March 2019) - Bhandari, Deepak; Udupi Bidkar, Prasanna; Adinarayanan, S; Narmadhalakshmi, K; Srinivasan, S
Abstract: Background: The standard methods for measuring intracranial pressure (ICP) are invasive in nature. Non invasive methods such as ONSD may help circumvent these complications and may serve as a surrogate marker for increased ICP. The primary aim of this study was to assess the ONSD (optic nerve sheath diameter) changes using ultrasonography (USG) and computed tomography (CT) scan in hydrocephalus patients before and after the insertion of VP shunt. Materials and methods: A prospective observational study was conducted among 69 patients undergoing VP shunt surgery between the ages of 2 to 60 years. ONSD variation was measured by USG and CT scan both before and after the surgery. The difference in the pre-operative and post-operative ONSD measurement was analyzed using a paired t-test. Whereas, the measurements of ONSD were compared for agreement between two modalities (USG and CT) using Interclass correlation (ICC) and Bland Altman graph plot. Results: Among 69 patients 38 were males, 31 were females and 12 were under the age of 10 years. In the adult group, average preoperative and postoperative ONSD measurement by USG was 5.80 ± 0.63 mm and 4.52 ± 0.72 (p < 0.001) and by CT was 5.77 ± 0.83 mm and 4.49 ± 0.76 mm (p < 0.001) respectively. Similarly, in the pediatric population, average preoperative and postoperative ONSD measurement by USG was found to be 4.76 ± 1.14 mm and 3.90 ± 1.08 mm and by CT was found to be 4.75+/-1.11 mm and 3.85 ± 1.09 mm respectively (p <0.001). Conclusion: In patients with hydrocephalus undergoing VP shunt surgery, we found a significant reduction in ONSD after the shunt insertion in both pediatric and adult population. We also found a good correlation between the USG and CT scan measurements of ONSD.